Foremost place to buddhism and its implications in sri lanka - Kosalai, M.; Bosco, D.M. (University of Jaffna, 2019)
The Article 9 of the Constitution of Sri Lanka is a unique provision as it places one religious belief, Buddhism under the protective arm of the State while assuring to all religions the rights granted by Articles 10 and 14(1)(e). This creates ambiguity as to the possibility of guaranteeing the absolute freedom of religion to all while giving first and foremost place to a particular religion or a belief. Indeed there are instances where Article 9 of the Constitution empowered organs of the government to curtail persons of other religions from exercising respective religious practices, manifestation and observance. As a result, whenever discussions held over addressing minority issues, Article 9 has been cited by all sides either for asserting its need for retention or the removal of it. The aim of this research paper is to examine the legal implications arising from the very nature of Article 9 of the Constitution, on minority religions. The research involves a qualitative study. For this purpose, the constitutional provisions are analyzed in depth in light of the judicial interpretations of the same provisions in appropriate cases.The paper considers the recent discussions and recommendations on Article 9 especially in the process to constitutional reform in order to suggest a better provision on religion for Sri Lanka.
Keywords: religious right; buddhism; constitution; foremost place; multi religious country